Evaluasi Kesehatan, Kebugaran, dan Tingkat Kemandirian Pada Lansia - Wahid, Wahyana Mujari; Ichsani, Ichsani; Rahman, Abdul; Arimbi, Arimbi; Zulfikar, Muhammad (Universitas PGRI Semarang, 2023)
Health and fitness are something that is important for someone, including elderly people. Apart from health and fitness, the level of independence in the elderly is also important as a reference for how an elderly person carries out daily activities. Independence is an ability or condition where an individual can manage or overcome his own interests without depending on other people. The aim of this service is to provide education and evaluation in providing an overview to the public about the profile or status of health, fitness and level of independence in the elderly. The community service method is carried out by conducting evaluations as well as education on how to maintain health and fitness, especially for the elderly. Evaluation of health, fitness and level of independence is carried out by measuring blood pressure and measuring VO2max. The level of independence is measured using the Activity Daily Living (ADL) instrument. Participants in this service were 40 elderly people consisting of 19 men and 21 women in collaboration with the NGO Development of Indonesian Sports Achievement and Health Potential (P3KORIN). The results of this service were obtained (1) The average blood pressure in male participants was 146/88 mmHg minute while in females it was 150/86 mmHg which was included in the hypertension category: (2) The average VO2 Max in males was 18.7 (ml.kg-1.min-1) while for women the average was 17 (ml.kg-1.min-1) which are both included in the very low category; (3) Activity Daily Living (ADL) is included in the good category with the average score for each gender being 5. In conclusion, the results of this service can be felt to be very useful in providing information and knowledge to partners (P3KORIN) about conditions and an overview of the health, fitness and level of independence of elderly people in the city of Makassar. This service also provides an overview of the factors that influence the health, fitness and independence of the elderly in the city of Makassar.